2015
DOI: 10.1158/1535-7163.mct-14-0155
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to Cabazitaxel

Abstract: We studied mechanisms of resistance to the novel taxane cabazitaxel in established cellular models of taxane resistance. We also developed cabazitaxel-resistant variants from MCF-7 breast cancer cells by stepwise selection in drug alone (MCF-7/CTAX) or drug plus the transport inhibitor PSC-833 (MCF-7/CTAX-P). Among multidrug resistant (MDR) variants, cabazitaxel was relatively less cross-resistant than paclitaxel and docetaxel (15 vs. 200-fold in MES-SA/Dx5 and 9 vs. 60-fold in MCF-7/TxT50, respectively). MCF-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 39 publications
1
61
0
2
Order By: Relevance
“…P-gpexpressing sublines were derived from the corresponding non-P-gp-expressing parental tumor cell lines by selection with different anticancer drugs (2,9,22). We also observed that triptolide nearly equipotently killed human pancreatic cancer Capan-1 and Ewing sarcoma SK-ES-1 cells and PARP inhibitor simmiparibselected resistant variants Capan-1/SP (RF: 0.84) and SK-ES-1/SP (RF: 1.36), and these variants did not express detectable drug transporters, including P-gp, MRP1, or BRCP (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P-gpexpressing sublines were derived from the corresponding non-P-gp-expressing parental tumor cell lines by selection with different anticancer drugs (2,9,22). We also observed that triptolide nearly equipotently killed human pancreatic cancer Capan-1 and Ewing sarcoma SK-ES-1 cells and PARP inhibitor simmiparibselected resistant variants Capan-1/SP (RF: 0.84) and SK-ES-1/SP (RF: 1.36), and these variants did not express detectable drug transporters, including P-gp, MRP1, or BRCP (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated triptolide potency in P-gp-expressing cell variants, including doxorubicin-selected variants, MES-SA/DX5 (22), and K562/A02 (2), and vincristine-selected KB/VCR (9). These sublines were resistant to agents used for their establishment, respectively as depicted in Fig.…”
Section: Triptolide Kills Mdr Cells Effectivelymentioning
confidence: 99%
“…Interestingly, washing did not impact the intracellular concentration of the drug, unlike Docetaxel-treated MCF-7 cells which demonstrated 50% concentration of drug postwashing, indicating that Cabazitaxel is better retained and thusly efficacious inside cells (Azarenko et al, 2014). Despite this improvement in intracellular retention, MDR-resistant MCF-7 variant cells still demonstrated resistance to the effects of Cabazitaxel although it was lower than that observed for Paclitaxel and Docetaxel (Duran et al, 2014).…”
Section: "Pumping" Issuesmentioning
confidence: 84%
“…Increased expression of the isotype βIII-tubulin has been clinically demonstrated for lung, breast, and ovarian cancers; in addition, overexpression of the βIII-tubulin isoform has been associated with progression to mCRPC, and is predictive not only of Docetaxel efficacy ( Fig. 3B; Ploussard et al, 2010;Terry et al, 2009), but also of Cabazitaxel to therapeutic resistance (Duran et al, 2014).…”
Section: Tubulin Mutationsmentioning
confidence: 98%
See 1 more Smart Citation